Optimization of the Amount of Zinc in the Graphitization Reaction for Radiocarbon AMS Measurements at LAC-UFF. Issue 3 (26th July 2016) - Macario, Kita D; Oliveira, Fabiana M; Moreira, Vinicius N; Alves, Eduardo Q; Carvalho, Carla; Jou, Renata M; Oliveira, Maria Isabela; Pereira, Bruna B; Hammerschlag, Izabela; Netto, Bruna; Seixas, Amanda P; Malafaia, João Vitor P; et al.
Abstract: The Radiocarbon Laboratory of the Universidade Federal Fluminense, in Brazil, has been successfully applying the zinc reduction method for graphitization of carbon samples since the development of its early protocols in 2009. Successive methodological research aiming to improve and, ultimately, optimize the precision and accuracy of our results indicates that graphitization temperatures as low as 460°C promote erratic 13 C isotopic fractionation, but an approximately constant fractionation of about –5‰ is achieved at 520°C. In this work, we present isotope ratio mass spectrometry (IRMS) δ 13 C results for 14 C reference materials graphitized at 550°C with variable amounts of zinc. Based on the results obtained from the addition of 20, 35, and 50 mg of zinc, we conclude that a slightly lower variation in 13 C isotope fractionation during graphitization is obtained with less zinc. Moreover, the average isotopic fractionation is not altered by increasing the graphitization temperature from 520°C to 550°C.